Rise, fall and resurrection of chromosome territories: a historical perspective Part II. Fall and resurrection of chromosome territories during the 1950s to 1980s. Part III. Chromosome territories and the functional nuclear architecture: experiments and m - T Cremer; C Cremer (European Journal of Histochemistry, 2009)
Part II of this historical review on the progress of nuclear architecture studies points out why the original hypothesis of chromosome territories from Carl Rabl and Theodor Boveri (described in part I) was abandoned during the 1950s and finally proven by compelling evidence forwarded by laser-uvmicrobeam studies and in situ hybridization experiments. Part II also includes a section on the development of advanced light microscopic techniques breaking the classical Abbe limit written for readers with little knowledge about the present state of the theory of light microscopic resolution. These developments have made it possible to perform 3D distance measurements between genes or other specifically stained, nuclear structures with high precision at the nanometer scale. Moreover, it has become possible to record full images from fluorescent structures and perform quantitative measurements of their shapes and volumes at a level of resolution that until recently could only be achieved by electron microscopy. In part III we review the development of experiments and models of nuclear architecture since the 1990s. Emphasis is laid on the still strongly conflicting views about the basic principles of higher order chromatin organization. A concluding section explains what needs to be done to resolve these conflicts and to come closer to the final goal of all studies of the nuclear architecture, namely to understand the implications of nuclear architecture for nuclear functions.